2000
DOI: 10.1123/jab.16.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hindlimb Suspension with Stretched or Shortened Muscle Length on Contractile Properties of Rat Soleus

Abstract: The effects of chronic stretching or shortening of the soleus muscle of adult rats during hindlimb suspension on muscle mass and contractile properties were studied. Rats suspended with the ankle joint immobilized in either a dorsiflexed (Susp-DF. soleus stretched), a plantarflexed position (Susp-PF, soleus shortened), or without immobilization (Susp-Free. soleus shortened) were compared with cage control rats. Suspension-related muscle atrophy was prevented in Susp-DF. The relative muscle weight in Susp-PF wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…During suspension, the ankle joint gradually assumes the position of plantar-flexion 7) , and SOL is shortened approximately 10 mm and EDL is lengthened 38) . It has been reported that atrophy of plantar flexors during suspension was prevented by fixation of the ankle joint in the dorsi-flexion position and passive stretch 39) . This means that weight-bearing during suspension induces passive dorsi-flexion of the ankle joint, leading to lengthening of SOL.…”
Section: Discussionmentioning
confidence: 99%
“…During suspension, the ankle joint gradually assumes the position of plantar-flexion 7) , and SOL is shortened approximately 10 mm and EDL is lengthened 38) . It has been reported that atrophy of plantar flexors during suspension was prevented by fixation of the ankle joint in the dorsi-flexion position and passive stretch 39) . This means that weight-bearing during suspension induces passive dorsi-flexion of the ankle joint, leading to lengthening of SOL.…”
Section: Discussionmentioning
confidence: 99%
“…Tension is not developed by shortened plantarflexors, even when EMG is present [27]. A suspension-related atrophy of plantarflexors was prevented when the muscles were stretched passively by plaster fixing of the ankle joint at a dorsiflexed position [30]. It is also indicated that forced contraction through electrical stimulation is not beneficial if the muscles are shortened and tension is not developed.…”
Section: Experiments Imentioning
confidence: 99%
“…Animal experiments performed in the early 1970s (Tabary et al, 1972;Williams and Goldspink, 1973) and later (Ohira et al, 2000) showed a loss of sarcomeres in series when muscles are immobilised in a shortened position. In humans, one common condition that places muscle-tendon units (MTUs) in a shortened position is high heel (HH) wearing.…”
Section: Introductionmentioning
confidence: 99%